Completeness and accuracy of International Classification of Disease (ICD) external cause of injury codes in emergency department electronic data. Issue 6 (3rd December 2007) - Hunt, P R; Hackman, H; Berenholz, G; McKeown, L; Davis, L; Ozonoff, V
Abstract : The accuracy of external cause of injury codes (E codes) for work-related and non-work-related injuries in Massachusetts emergency department data were evaluated. Medical records were reviewed and coded by a nosologist with expertise in E coding for a stratified random sample of 1000 probable work-related (PWR) and 250 probable non-work-related (PNWR) cases. Cause of injury E codes were present for 98% of reviewed cases and accurate for 65% of PWR cases and 57% of PNWR cases. Place of occurrence E codes were present in less than 30% of cases. Broad cause of injury categories were accurate for about 85% of cases. Non-specific categories (not elsewhere classified, not specified) accounted for 34% of broad category misclassifications. Among specified causes, machinery injuries were misclassified most often (39/60, 65%), predominantly as cut/pierce or struck by/against. E codes reliably identify the broad mechanism of injury, but inaccuracies and incompleteness suggest areas for training of hospital admissions staff, providers, and coders.